Analisis Hukum Tanggung Jawab dan Implikasi Persekutuan: Studi pada Persekutuan Perdata, Firma, dan CV - Adam, Chelsea Kairadinda; Vazkya, Ni Komang Revalina Senandung; Adam, Shaquille Rashaan Putra; Rizkiyansyah, Muhammad Rasyid Fasya; S, Sulastri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The legal liability of partners in civil partnerships, firms, and CVs is also an important issue. Each type of partnership has a different liability structure. For example, in a CV, a general partner has full responsibility for the company's debts, while a limited partner is only responsible up to the capital invested. Lack of understanding regarding the limits of each partner's authority can lead to legal disputes that are detrimental to all parties. With their respective characteristics, objectives, and legal consequences, civil partnerships, firms, and commanditaire vennootschap (CV) are very important forms of partnership in Indonesian business law. Because each involves an agreement between parties who want to share the profits of a joint venture, these three types of partnerships are closely related to each other. Each has specific features that can be selected according to the needs and objectives of the company. Civil Partnerships, Firms, and CVs offer a variety of structures that can be tailored to the type of business and the number of tasks desired by the partners.